(3GdYdGbGJ GdEbJUGOjI GdOhdjI (B:s (3eONd dOQGSI GdeHGOF GdCSGSjI GdMGceI ddEbJUGO GdOhdj HeQGYGI GdJWhQGJ GdeSJLOI GdfGJLI Yf JfGej eXGgQ GdYhdeI aj fWGbg (B/s - (3MTjT, YGOd CMeOs; (3TgGH, eLOj eMehO s ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2005)
(3CgejI heGgjI GdEbJUGO GdOhdj heXGgQ GdeYGedGJ GdEbJUGOjI GdbGFeI aj eMjW GdCShGb GdOhdjI(B-(3GdYhGed GdeShZI dbjGe GdYdGbGJ GdEbJUGOjI GdOhdjI hGdeDTQGJ GdOGdI Ydi GdCgejI GdfSHjI ddJLGQI GdNGQLjI HGdfSHI ddEbJUGO Gdbhej(B-(3GdedGeM hGdNUGFU GdeMOOI deYGde GdYdGbGJ GdEbJUGOjI GdOhdjI GdeYGUQI habG ddeJZjQGJ GdWGQFI Ydi HjFI GdEbJUGO GdYGdej(B-(3GdfXQjGJ GdJbdjOjI GdeHQQI dhLhO GdJLGQI GdNGQLjI aj eMjW GdYdGbGJ GdEbJUGOjI GdOhdjI(B-(3fXQjGJ GdJLGQI GdOhdjI GdMOjKI(B-(3GdEWGQ GdeDSSj GdehVM ddeYGedGJ GdEbJUGOjI(B-(3JShjIGdeOahYGJ GdOhdjI(B-(3UfOhb GdfbO GdOhdj(B-(3GdSjGSGJ GdJLGQjI GdehLgI ddJHGOd GdOhdj (B-(3JWhQ GdeHGOF GdMGceI ddYdGbGJ GdEbJUGOjI GdOhdjI(B-(3GdEWGQ GdeDSSj dVeGf GSJeQGQjI eXGgQ GdYhdeI aj eMjW GdYdGbGJ GdEbJUGOjI GdOhdjIs
Keywords: (3GdEbJUGO GdOhdjs; (3GdJLGQI GdNGQLjIs; (3GdYdGbGJ GdEbJUGOjI GdOhdjIs